2003
DOI: 10.1085/jgp.200308863
|View full text |Cite
|
Sign up to set email alerts
|

pH Changes in the Invaginating Synaptic Cleft Mediate Feedback from Horizontal Cells to Cone Photoreceptors by Modulating Ca2+ Channels

Abstract: Feedback from horizontal cells (HCs) to cone photoreceptors plays a key role in the center-surround–receptive field organization of retinal neurons. Recordings from cone photoreceptors in newt retinal slices were obtained by the whole-cell patch-clamp technique, using a superfusate containing a GABA antagonist (100 μM picrotoxin). Surround illumination of the receptive field increased the voltage-dependent calcium current (ICa) in the cones, and shifted the activation voltage of ICa to negative voltages. Exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
227
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(249 citation statements)
references
References 61 publications
(90 reference statements)
19
227
1
2
Order By: Relevance
“…The susceptibility of I Ca to changes in pH was established earlier by Barnes and Bui (1991) and Barnes et al (1993). In the newt retina, Hirasawa and Kaneko (2003) found that strong pH buffering largely eliminated the surround-induced shift in the cone I Ca . They postulate that in an intact preparation, the pH of the synaptic cleft is more acidic (by about 0.2 pH unit) than the extracellular pool, and that surround illumination, by hyperpolarizing the horizontal cell, reduces the proton level in the cleft.…”
Section: Feedback From Horizontal Cells To Conesmentioning
confidence: 74%
See 1 more Smart Citation
“…The susceptibility of I Ca to changes in pH was established earlier by Barnes and Bui (1991) and Barnes et al (1993). In the newt retina, Hirasawa and Kaneko (2003) found that strong pH buffering largely eliminated the surround-induced shift in the cone I Ca . They postulate that in an intact preparation, the pH of the synaptic cleft is more acidic (by about 0.2 pH unit) than the extracellular pool, and that surround illumination, by hyperpolarizing the horizontal cell, reduces the proton level in the cleft.…”
Section: Feedback From Horizontal Cells To Conesmentioning
confidence: 74%
“…New evidence on this point (Hirasawa and Kaneko, 2003) suggests that pH may play a crucial role. The susceptibility of I Ca to changes in pH was established earlier by Barnes and Bui (1991) and Barnes et al (1993).…”
Section: Feedback From Horizontal Cells To Conesmentioning
confidence: 99%
“…Although we show that I Ca also facilitates in cones, this appears not to be the origin of the Ca 2+ / CaM-dependent recovery process we describe here, as I Ca facilitation is unperturbed by the CaM inhibitors that slow recovery. However, because protons play a key role in regulating photoreceptor I Ca (DeVries 2001; Hirasawa and Kaneko, 2003), a similar mechanism may contribute to recovery from synaptic depression under conditions with reduced extracellular pH buffering, e.g., with a bicarbonate-based saline solution. In hair cells, although synaptic transmission facilitates when resting intracellular [Ca 2+ ] is reduced with a hyperpolarized holding potential, depression dominates at physiological resting potentials .…”
Section: Potential Molecular Mechanisms Of Ca 2+ /Cam Effectsmentioning
confidence: 99%
“…Finally, no highaffinity transport of [ 3 H] GABA or GABA analogs by horizontal cells has been reported for any adult mammalian retina (Ehinger, 1977;Blanks & Roffler-Tarlov, 1982;Mosinger and Yazulla, 1985;Wä ssle & Chun, 1988Löhrke et al, 1994). More recently, alternative mechanisms of horizontal cell feedback involving electrical resistance or ephaptic feedback onto cones in goldfish (Kamer- Kamermans and Fahrenfort, 2004) and a pH-dependent modulation of cone calcium channels in newts (Hirasawa and Kaneko, 2003) have been proposed. Proton release that occurs with vesicular release may contribute to an increase in proton concentration in the synaptic cleft that produces the shift in the currentvoltage relation of the calcium current (Hirasawa and Kaneko, 2003).…”
Section: Transmitter Release From Horizontal Cellsmentioning
confidence: 99%